Metabolomic Analysis of Platelets of Patients With Aspirin Non-Response - Chiang, Jiun-Yang; Lee, Sheng-Han; Chen, Yen-Ching; Wu, Cho-Kai; Chuang, Jing-Yuan; Lo, Shyh-Chyi; Yeh, Huei-Ming; Yeh, Shih-Fan Sherri; Hsu, Cheng-An; Lin, Bin-Bin; Chang, Pi-Chu; Chang, Chih-Hsin; et al. (Frontiers in Pharmacology, 2019)
Background: Aspirin is the most commonly used antiplatelet agent for the prevention of cardiovascular diseases. However, a certain proportion of patients do not respond to aspirin therapy. The mechanisms of aspirin non-response remain unknown. The unique metabolomes in platelets of patients with coronary artery disease (CAD) with aspirin non-response may be one of the causes of aspirin resistance. Materials and methods: We enrolled 29 patients with CAD who were aspirin non-responders, defined as a study subject who were taking aspirin with a platelet aggregation time less than 193 seconds by PFA-100, and 31 age- and sex-matched patients with CAD who were responders. All subjects had been taking 100 mg of aspirin per day for more than 1 month. Hydrophilic metabolites from the platelet samples were extracted and analyzed by nuclear magnetic resonance (NMR). Both 1D 1H and 2D J-resolved NMR spectra were obtained followed by spectral processing and multivariate statistical analysis such as partial least squares discriminant analysis (PLS-DA). Results: Eleven metabolites were identified. The PLS-DA model could not distinguish aspirin non-responders from responders. those with low serum glycine level had significantly shorter platelet aggregation time ( mean 175.0 sec) compared with those with high serum glycine level ( 259. 5 sec). However, this association became non-significant after correction for multiple tests. Conclusions: The hydrophilic metabolic profile of platelets was not different between aspirin non-responders and responders. An association between lower glycine levels and higher platelet activity in patients younger than 65 years suggest an important role of glycine in the pathophysiology of aspirin non-response.